Musées d'Art Vivant. - Wallraf-Richartz Museum, Keulen; Musée des Beaux-Arts, Lille; Museum Boymans-van Beuningen, Rotterdam; Museo Civico, Turin; Musée des Beaux-Arts, Liège (Liège : Musée des Beaux-Arts, 1964)
Baumeister, Willi ; Beckmann, Max ; Gilles, Werner ; Heckel, Erich ; Hoehme, Gerhard ; Mettel, Hans ; Kirchner, Ernst ; Modersohn-becker, Paula ; Nay, Ernst-Wilhelm ; Trier, Hann ; Schmidt-Rottluff, Karl ; Nolde, Emil ; etc.
Musées d'Art Vivant, Wallraf-Richartz Museum, Keulen / Musée des Beaux-Arts, Lille / Museum Boymans-van Beuningen, Rotterdam / Museo Civico, Turin / Musée des Beaux-Arts, Liège, 14 mai - 14 juin 1964
boek